Formulation and Antibacterial Activity of Liquid Soap Containing Ketapang (Terminalia catappa L.) Leaves Extract - Asiska Permata Dewi; Dini Mardhiyani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Ketapang (Terminalia catappa L.) is traditionally used by the community to treat the skin's infections caused by bacteria or fungi. In this study, T. catappa leaves extract was added to the liquid soap formula as an antibacterial. The purpose of this study was to determine the secondary metabolite compounds contained in T. catappa leaves extract, physical evaluation of the preparation, and antibacterial activity of liquid soap. Liquid soap formula was made with various concentrations of T. catappa leaves extract F0 (0%), F1 (1%), F2 (2%), and F3 (3%). The resulting soap was evaluated for organoleptic, pH, high foam, homogeneity, irritation, and its activity against Staphylococcus aureus, Staphylococcus epidermidis, and Escherichia coli using the disc diffusion method. The results showed that the T. catappa leaves extract contained flavonoids, tannins, saponins, and triterpenoids. The liquid soap formula F0 was clear, while F1, F2, and F3 had the characteristics of brown-dark brown, homogeneous, pH between 4.6-5.2, foam stability between 67-72%, which was not significantly different and stable after five minutes of testing, and it did not irritate the skin. Terminalia catappa leaves extracts liquid soap has antibacterial activity at a concentration of 1%, 2%, and 3%, with the largest inhibition zone diameter produced by S. aureus.